Which countries are prepared to green their coal-based steel industry with electricity? - Reviewing climate and energy policy as well as the implementation of renewable electricity. (June 2021) - Arens, Marlene; Åhman, Max; Vogl, Valentin
Abstract: Global steel production is currently dependent on coal and capital-intensive production facilities with long economic lifetimes. While the Paris Agreement means carbon neutrality must be reached globally by 2050–2070, with negative emissions thereafter, coal-based steel production today accounts for around 8% of global energy-related CO2 emissions. Its production may stabilize or even decline in industrialized countries, but it will increase significantly in the emerging economies. In the past, the focus of CO2 reduction for steel has been on moderate emissions reductions through energy efficiency measures and on exploring carbon capture and storage. However, as (1) the cost of renewable electricity is declining rapidly, (2) carbon capture and storage has not materialized yet, and (3) and more and more countries set deep emission reduction targets, electricity- and hydrogen-based steelmaking has gathered substantial momentum over the past half-decade. Given the short time frame and the sector's deep carbon lock-in, there is an urgent need to understand the national climate and energy policy as well as the current implementation of low-CO2 and renewable electricity that would enable a shift from coal-based to electricity-based steelmaking. In this paper, we first identify the countries that are likely to be major steel producers in the future and thus major CO2 -emitters. Then we map medium- and long-term CO2 reduction and renewable targets as well as the current share of low-CO2 and renewable electricity by country. Based on these data, we develop a set of indicators that map the readiness of steel-producing countries for a sustainable transition. Our findings show that although binding long-term CO2 reduction targets are being implemented, medium-term CO2 reduction do not yet affect coal based steel production. Overall, the global steel industry seems not be on track yet, though differences between steel producing countries are large. Common shortcomings across countries are a lack of access to renewable electricity and a lack of demanding medium-term CO2 reduction targets. The paper ends with recommendations on how to enable a low-carbon transition of the global steel industry in line with the Paris Agreement. Highlights: Four major steel producing countries have committed to carbon neutrality by mid-century. 2030 CO2 reduction targets do not affect coal-based steelmaking. Access to renewable electricity is limited in most countries. One third of the steelmaking countries strongly rely on coal for their economy.